2016
DOI: 10.4236/ajps.2016.71024
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Carbon Dioxide Level Suppresses Nutritional Quality of Lettuce and Spinach

Abstract: Rising global CO 2 levels are a major factor that impacts not only the environment but also many plant functions including growth, productivity and nutritional quality. The study examined the impact of elevated [CO 2 ] on nutritional quality and growth characteristics of lettuce (Lactuca sativa) and spinach (Spinacia oleracea). Elevated [CO 2 ] decreased the concentration of many important nutrients including nitrogen (protein), potassium and phosphorus in the edible parts of both lettuce and spinach. The nitr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
26
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 32 publications
4
26
0
Order By: Relevance
“…Additionally, CO 2 enrichments decreased protein concentration (Fig. f), consistent with several other studies in grains and other vegetables . Although cucumber is not the main protein source, the decreased protein concentration in both vegetables and grain crops potentially accelerates the imbalance in energy and protein uptake, particularly for vegans …”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Additionally, CO 2 enrichments decreased protein concentration (Fig. f), consistent with several other studies in grains and other vegetables . Although cucumber is not the main protein source, the decreased protein concentration in both vegetables and grain crops potentially accelerates the imbalance in energy and protein uptake, particularly for vegans …”
Section: Discussionsupporting
confidence: 90%
“…wheat, rice, and sorghum) and vegetables (e.g. lettuce, sweet pepper, and carrot and turnip). This similarity gives us a warning that the deficiency of Fe and Zn could possibly impose an inevitable threat to human nutrition from the consumption of either grain crops or vegetables if breeders or producers continue focusing on increasing vegetable yield in the future.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Loladze () demonstrated that e[CO 2 ] reduced wheat grain protein and nitrogen concentrations. Similarly, studies by Taub et al (), De Graaff, Van Groenigen, Six, Hungate, and van Kessel (), Conroy (), and Giri, Armstrong, and Rajashekar () investigated the response of grain protein to e[CO 2 ] under different N regimes. Several experiments were carried out to investigate the responses of biomass and productivity to e[CO 2 ] among different functional groups (Hooper & Vitousek, ; Reich et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Diminished nitrogen content of plants, which mostly reflects on their protein content, is a major concern as it plays an important role in the human diet. Malnutrition and showed a significant decrease in a number of major and micronutrients including protein and zinc [36]. In a meta-analysis of nutritional quality of many food crops as affected by elevated CO 2 , Loladze [37] showed that the overall pattern in many C 3 plants was that elevated CO 2 depressed not only nitrogen but many other nutrients including iron, zinc, calcium, potassium, sulfur and other micronutrients.…”
Section: Plant Growth and Major Nutrientsmentioning
confidence: 99%